Changes in Metabolism and Caloric Intake after Sport Concussion: A Case Series. Issue 12 (2020) - Daniell, Brooke; Bernitt, Candace; Walton, Samuel R.; Malin, Steven K.; Resch, Jacob E.
ABSTRACT: Purpose: Resting metabolic rate (RMR) changes as a result of moderate and severe traumatic brain injury in humans. However, the effect of sport concussion (SC) on RMR and subsequent food intake is unknown. The purpose of this study was to examine how SC affected energy expenditure, caloric intake (CI), and energy balance (EBal) in student-athletes. Methods: In this case series, 10 student-athletes (3 high school males, 3 high school females, 2 collegiate males, and 2 collegiate females) were assessed ⩽72 h after SC (T1), 7 d after T1 (T2), and 7 d after T2 (T3) by undergoing indirect calorimetry and recording diet and step count for 3 d around each assessment. RMR, total energy expenditure (TEE), CI, and EBal were evaluated across time using repeated-measures ANOVA. Main outcomes were related to symptoms using Spearman's ρ correlations. Results: RMR ( F (2) = 1.52, P = 0.24, η 2 = 0.15) and TEE ( F (2) = 2.29, P = 0.13, η 2 = 0.20) were not statistically different over time. However, males experienced increased RMR (mean difference, T3 − T1 = 206 kcal·d −1 ) compared with a decline for females (T3 − T1 = −32 kcal·d −1 ). CI decreased from T2 to T3 by approximately 385 kcal in both males and females ( F (2) = 4.73, P = 0.02, η 2 = 0.35). EBal changed ( F (2) = 4.35, P = 0.03, η 2 = 0.33) from overeating (T1 = 593 kcal surplus) to relative balance (T3 = 61 kcal surplus). Conclusions: Although overall energy expenditure was not altered over time after concussion, a pattern suggesting sex differences was present. Participants initially overconsumed calories relative to TEE; however, this disparity declined over time to the point of EBal by the third assessment.